2014
DOI: 10.3109/02770903.2014.955191
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychological distress mediates the relationship between asthma and physician visits in a population-based sample of adolescents

Abstract: These findings suggest that maternal psychological distress is associated with increased physician visits, regardless of adolescents' general health. Lowering maternal psychological distress may serve to reduce health care utilization and costs among adolescents with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Negative emotions such as stress can increase the release of histamine or other allergic inflammatory mediators in the body, which inhibit reactivity of sympathetic nerves, stimulate excitability of the vagus nerve, and induce or exacerbate asthma attacks ( 39 ). A long-term follow-up study in Canada with 4,025 mothers and their children (3–5 days after child birth, at 6 months, 5 years, and 14 years) found that 14 year-old children with asthma ( n = 1,457) had more clinical visits (4.1 vs. 2.2) than those without asthma ( n = 2,568), that mothers of children with low DSSI scores were more likely to reach anxiety and depression thresholds (15 vs. 12%), and that the psychological pressure of mothers was associated with the frequencies of children's clinical visits for asthma (accounting for 25% of the variations in adolescent clinical visits) ( 40 ). On the other hand, applying scientific methods to educate children to maintain good living habits and reasonable recreational activities are also conducive to maintaining their inner happiness and helping them comply with medical treatments ( 41 ).…”
Section: Protection Of Children With Asthma During the Pandemicmentioning
confidence: 99%
“…Negative emotions such as stress can increase the release of histamine or other allergic inflammatory mediators in the body, which inhibit reactivity of sympathetic nerves, stimulate excitability of the vagus nerve, and induce or exacerbate asthma attacks ( 39 ). A long-term follow-up study in Canada with 4,025 mothers and their children (3–5 days after child birth, at 6 months, 5 years, and 14 years) found that 14 year-old children with asthma ( n = 1,457) had more clinical visits (4.1 vs. 2.2) than those without asthma ( n = 2,568), that mothers of children with low DSSI scores were more likely to reach anxiety and depression thresholds (15 vs. 12%), and that the psychological pressure of mothers was associated with the frequencies of children's clinical visits for asthma (accounting for 25% of the variations in adolescent clinical visits) ( 40 ). On the other hand, applying scientific methods to educate children to maintain good living habits and reasonable recreational activities are also conducive to maintaining their inner happiness and helping them comply with medical treatments ( 41 ).…”
Section: Protection Of Children With Asthma During the Pandemicmentioning
confidence: 99%